DIPLOMASI INDONESIA TERHADAP UNESCO DALAM MERESMIKAN TARI SAMAN SEBAGAI WARISAN BUDAYA INDONESIA - Andini Tria Nastiti; Tri Joko Waluyo (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2015)
This study describes about Indonesian Diplomacy for UNESCO Paten’s Saman Dance. It has already been fact to be forced by every nation and state. Nowadays, threat comes from internal and external. From internal, young generations see Saman Dance as an old culture which is too complicated to learn. Other reason is endangerment of the originality Saman Dance caused globalization. And from external, there are so many claims for Indonesian culture.This research shows how the diplomacy of Indonesia which involved many party including the public and other government agencies to get Saman Dance as Indonesian Official Heritage Culture by UNESCO and finally they made it since UNESCO inscribes Indonesia Saman Dance on the list of the Intangible Cultural Heritage of Humanity throgh the meeting on November 24th, 2011 in Bali.Multi-track Diplomacy used to foster peace between state or particular interest. Its authenticity on the fact that it realis on various contributions from Goverment and non Goverment. This Article will explain how the multitrack diplomacy work to help the Indonesian Government’s push UNESCO to get Paten Indonesia’s Saman Dance.Keyword: Diplomacy, Paten, Multi-track Diplomacy, Saman Dance, Cultural Heritage and UNESCO